2015
DOI: 10.1128/jb.00402-15
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation by the Short-Chain Fatty Acyl Coenzyme A Regulator (ScfR) PccR Controls Propionyl Coenzyme A Assimilation by Rhodobacter sphaeroides

Abstract: Propionyl coenzyme A (propionyl-CoA Rhodobacter sphaeroides belongs to the purple nonsulfur bacteria, a physiologically related group of phototrophic bacteria known for their metabolic versatility (1). Given their natural abundance in anaerobic portions of stagnant water, purple nonsulfur bacteria are adept at using light as a source of energy during anaerobic growth while acquiring carbon from fermentation products, such as propionate. Despite the abundance of propionate in its natural environment, R. sphaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…The pccBC and pccA operons are induced by propanol and propionate in S. erythraea. It was reported that propionyl-CoA carboxylases were upregulated when propanol or propionate was added to microorganisms (18,19). Propanol is converted into propionate, which is subsequently metabolized to propionyl-phosphate or propionyl-CoA by propionate kinase or acetyl/propionyl-CoA synthetase (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The pccBC and pccA operons are induced by propanol and propionate in S. erythraea. It was reported that propionyl-CoA carboxylases were upregulated when propanol or propionate was added to microorganisms (18,19). Propanol is converted into propionate, which is subsequently metabolized to propionyl-phosphate or propionyl-CoA by propionate kinase or acetyl/propionyl-CoA synthetase (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The transcriptional regulation of the genes encoding enzymes of the PCC pathway in bacteria remains unknown. Recently, Carter and Alber found that RSP_2186 (designated PccR) controls the transcription of the propionyl-CoA carboxylase gene in Rhodobacter sphaeroides (19). They defined a novel family of short-chain fatty acyl-CoA regulators (ScfRs) that modulate pathways for short-chain acyl-CoA assimilation in microorganisms, including PccR (PCC pathway for propionyl-CoA assimilation), MccR (MCC for propionyl-CoA assimilation), RamB (glyoxylate bypass for acetyl-CoA assimilation), and IbcR (for isobutyryl-CoA assimilation) (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, BkdR (21,23,26) takes part in regulating BCAA degradation. LrpG (33), PrpR (34), PccR (35), and PccD (29) participated in propionyl-CoA assimilation. In Mycobacterium, acetyl/propionyl-CoA carboxylase (accD1A1) and branched-chain ␣-keto acid dehydrogenase (bkdABC) exist in the same operon and are regulated by a regulator, BkaR, simultaneously (36).…”
Section: Figmentioning
confidence: 99%